Lithium-ion battery anode

A three-dimensional network of carbon nanotubes and amorphous carbon-coated nanosilicon anodes address the uniformity and stability issues of CNT-nanosilicon composites, providing improved electrochemical performance and flexibility in lithium-ion batteries.

JP7620295B2Active Publication Date: 2025-01-23TSINGHUA UNIVERSITY +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2023091631
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-06-10
Filing Date
2023-06-02
Publication Date
2025-01-23
Estimated Expiration
2043-06-02

AI Technical Summary

Technical Problem

The challenge of achieving a uniform composite of carbon nanotubes (CNTs) and nanosilicon in lithium-ion battery anodes is hindered by electrostatic repulsion due to similar negative zeta potentials, leading to agglomeration and poor electrochemical performance, including active material shedding and flexibility issues.

Method used

A three-dimensional network structure of carbon nanotubes with nanosilicon particles coated in amorphous carbon, combined with carbon nanotube functional layers, is formed by coating nanosilicon with a positively charged carbonizable polymer to achieve uniform dispersion and electrostatic attraction, enhancing mechanical support and electron transport.

Benefits of technology

The resulting anode exhibits improved cycle performance, flexibility, and reduced active material loss, with enhanced electrical conductivity and stability under mechanical stress, eliminating the need for additional adhesives and current collectors.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620295000001
    Figure 0007620295000001
  • Figure 0007620295000002
    Figure 0007620295000002
  • Figure 0007620295000003
    Figure 0007620295000003
Patent Text Reader

Abstract

To provide an anode for a flexible nano-silicon lithium-ion battery in which carbon nanotubes and nano-silicon in the anode are uniformly composited and the nano-silicon is difficult to agglomerate.SOLUTION: An anode 100 for a lithium-ion battery includes: a three-dimensional network structure 102 formed by a plurality of carbon nanotubes intertwined with each other; a plurality of nano-silicon particles 104 coated with amorphous carbon; and two carbon nanotube functional layers 106. The amorphous carbon is obtained by calcining a positively charged carbonizable polymer at high temperatures. The two carbon nanotube functional layers 106 are respectively located on two opposite surfaces of the three-dimensional network structure 102 of the carbon nanotube. The carbon nanotube functional layers 106 each comprise at least two super-aligned carbon nanotube films stacked and crossed with each other.SELECTED DRAWING: Figure 14
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to the field of lithium ion batteries, and in particular to a lithium ion battery anode comprising uniformly composited nanometer silicon and carbon nanotubes. [Background technology]

[0002] Silicon materials are ideal anode materials because of their very high theoretical specific capacity and abundant reserves. In recent years, with the rapid development of electronic devices, new requirements for the flexibility of electronic devices have been put forward. Therefore, the manufacture of flexible silicon anodes is very important. However, the violent volume change of silicon during repeated charging and discharging (cycling) of lithium-ion batteries can easily cause the electrode to burst or separate from the current collector, and the flexibility and poor electrical conductivity of silicon materials further restrict the application of silicon materials to lithium-ion batteries. Compared with traditional silicon materials, nanosilicon can withstand mechanical stress caused by volume change and effectively avoid particle crushing. Because the size of nanosilicon is nanoscale, the electron transfer path can be shortened, improving the electrical conductivity of nanosilicon. However, nanosilicon is relatively prone to aggregation.

[0003] Carbon nanotubes (CNTs) are characterized by a high aspect ratio, clean surface, strong intermolecular forces, and excellent mechanical, electrical, and thermal properties. Macroscopic materials made from carbon nanotubes, such as carbon nanotube films and carbon nanotube sponges, show excellent electrothermal properties and mechanical flexibility. Therefore, by combining CNTs and nanosilicon, a flexible nanosilicon anode with better electrical conductivity can be obtained. [Prior art documents] [Non-patent literature]

[0004] [Non-Patent Document 1] Kaili Jiang, Qunqing Li, Shoushan Fan, “Spinning continuous carbon nanotube yarns”, Nature, 2002, volume 419, p.801 [Patent documents]

[0005] [Patent Document 1] China Patent Publication No. 1483667 Summary of the Invention [Problem to be solved by the invention]

[0006] However, the zeta potential of CNTs is negative, and the zeta potential of nanosilicon is also negative, so that CNTs and nanosilicon are repelled by electrostatic interaction. It is difficult to obtain a uniform composite of CNTs and nanosilicon, and it is also difficult to obtain a uniform anode for lithium-ion batteries composed of CNTs and nanosilicon. In addition, the active material on the surface of the lithium-ion anode of the conventional technology is easily shed, which leads to a decrease in the electrochemical performance of the lithium-ion battery.

[0007] To solve the above technical problems, it is necessary to provide a flexible nanosilicon lithium ion battery anode, in which the CNTs and nanosilicon in the flexible nanosilicon lithium ion battery anode are uniformly combined, and the nanosilicon does not aggregate. [Means for solving the problem]

[0008] The anode of the lithium ion battery includes a three-dimensional network structure of carbon nanotubes, a plurality of nanosilicon particles coated with amorphous carbon, and two carbon nanotube functional layers. The three-dimensional network structure of carbon nanotubes is composed of a plurality of intertwined carbon nanotubes, and the two surfaces of the three-dimensional network structure of carbon nanotubes are defined as a first surface and a second surface, which are opposite to each other. The nanosilicon particles coated with amorphous carbon are dispersed in the three-dimensional network structure of carbon nanotubes and attached to the surfaces of the carbon nanotubes in the three-dimensional network structure of carbon nanotubes, and the amorphous carbon is obtained by baking a positively charged carbonizable polymer at a high temperature. The two carbon nanotube functional layers are laid on the first surface and the second surface of the three-dimensional network structure of carbon nanotubes, respectively, to position the three-dimensional network structure of carbon nanotubes between the two carbon nanotube functional layers, and the carbon nanotube functional layers include at least two layers of super-aligned carbon nanotube films arranged in a stacked and crossed manner.

[0009] The mass loading of the nanosilicon particles is 1.2 mg / cm 2 ~2mg / cm 2 It is.

[0010] The anode of the lithium ion battery includes a three-dimensional carbon nanotube network structure and a plurality of nanosilicon particles coated with a positively charged carbonizing polymer, the three-dimensional carbon nanotube network structure being composed of a plurality of intertwined carbon nanotubes, the plurality of nanosilicon particles coated with a positively charged carbonizing polymer being dispersed in the three-dimensional carbon nanotube network structure and attached to the surfaces of the carbon nanotubes in the three-dimensional carbon nanotube network structure.

[0011] The carbon nanotube functional layer is formed on the first surface of the carbon nanotube film and the second surface of the carbon nanotube film are disposed on the second surface of the carbon nanotube film. Effect of the Invention

[0012] Compared with the prior art, the anode of the lithium ion battery provided by the present invention has a nanosilicon surface coated with a positively charged carbonized polymer or amorphous carbon obtained by baking a positively charged carbonized polymer at high temperature, so that the zeta potential of the carbon nanotube is negative, the carbon nanotube and the positively charged carbonized polymer are non-uniformly charged, and the carbon nanotube and the nanosilicon modified with the positively charged carbonized polymer are dispersed by their respective electrostatic repulsion forces and anchored by their mutual electrostatic attraction forces. Therefore, the nanosilicon whose surface is coated with a positively charged carbonized polymer is uniformly dispersed in the three-dimensional network structure formed by the carbon nanotube and can be well bonded to the carbon nanotube, and the nanosilicon coated with amorphous carbon formed by decomposing the positively charged carbonized polymer at high temperature is also dispersed in the three-dimensional network structure made of the carbon nanotube and can be well bonded to the carbon nanotube. The continuous three-dimensional network structure can simultaneously function as a mechanical support framework and a transport grid for electrons and lithium ions. The CNT functional layers located on the two surfaces of the three-dimensional carbon nanotube network structure can effectively reduce the detachment of active materials from the electrode surface, thereby making the lithium-ion battery have better cycle and charge performance. [Brief description of the drawings]

[0013] [Figure 1] 1 is a flowchart of a method for manufacturing a lithium-ion battery anode provided by an embodiment of the present invention. [Diagram 2] 1 shows a dispersion simulation diagram between nanosilicon and carbon nanotubes, and a dispersion simulation diagram between nanosilicon (SiPA) whose surface is coated with polyaniline and carbon nanotubes. [Diagram 3] FIG. 1 is a schematic diagram of the fabrication process of CNT@Si composite membrane and CNT@SiPA composite membrane provided by an embodiment of the present invention. [Figure 4] FIG. 2 is a schematic diagram of a carbon nanotube functional layer provided on both sides of a composite membrane according to an embodiment of the present invention. [Diagram 5] 1 is a scanning electron microscope photograph of a cross section of a lithium-ion battery anode obtained by a manufacturing method provided in an embodiment of the present invention. [Figure 6] 1A and 1B are thermogravimetric analysis (TGA) curves of SiPA0.01, SiPA0.005, and SiPA0.015 provided by embodiments of the present invention. [Figure 7] 13A and 13B are graphs of cycle performances of button batteries respectively assembled with CNT@Si, CNT@Si-membrane, CNT@SiPAC, and CNT@SiPAC-membrane anodes provided by embodiments of the present invention. [Figure 8] 1 is a graph showing the cycle performance of button batteries obtained by using the anodes of CNT@SiPAC0.01-film, CNT@SiPAC0.005-film, and CNT@SiPAC0.015-film in embodiments 1 to 3 of the present invention. [Figure 9] FIG. 13 shows the cycle capacity curves of the battery when the area loading of Si is 1.19 mg / cm2, 1.38 mg / cm2, 1.72 mg / cm2 and 1.99 mg / cm2 in the anode of the CNT@SiPAC-membrane provided by an embodiment of the present invention. [Figure 10]13 shows the power performance curves of cells composed of CNT@Si, CNT@Si-membrane, CNT@SiPAC, and CNT@SiPAC-membrane anodes provided by embodiments of the present invention. [Figure 11] 1 is a graph of the cycling performance of a SiPAC / / Li pouch battery provided by an embodiment of the present invention. [Figure 12] 13 shows the change curves of resistance according to the number of bending cycles when the Si slurry electrode and the CNT@SiPAC-film electrode provided by the embodiment of the present invention are subjected to 90° and 180° long cycle bending. [Figure 13] 1 is a voltage curve before and after bending of a SiPAC / / LFP pouch battery provided by an embodiment of the present invention. [Figure 14] FIG. 2 is a schematic structural diagram of a positive electrode of a lithium-ion battery provided by an embodiment of the present invention. [Figure 15] FIG. 2 is a schematic structural diagram of a positive electrode of another lithium-ion battery provided by an embodiment of the present invention. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0014] DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS Hereinafter, the embodiments of the technical solution of the present invention will be described in more detail with reference to the accompanying drawings and specific embodiments.

[0015] 1, the first embodiment of the present invention provides a method for manufacturing a positive electrode of a lithium-ion battery, the method for manufacturing a positive electrode of a lithium-ion battery includes the following steps:

[0016] Step S1: providing a nanosilicon material, and coating the surface of the nanosilicon material with a positively charged carbonizable polymer to obtain nanosilicon whose surface is coated with a positively charged carbonizable polymer.

[0017] Step S2: Provide a solvent and carbon nanotubes (CNTs), add the carbon nanotubes and nanosilicon coated with a positively charged carbonizable polymer to the solvent in a certain ratio, and perform ultrasonic dispersion to obtain a dispersion.

[0018] Step S3: The dispersion is vacuum filtered to obtain a composite film of CNTs and nanosilicon coated with a positively charged carbonizing polymer on the surface.

[0019] Step S4: A carbon nanotube functional layer is disposed on each of two opposing surfaces of the composite membrane, and the composite membrane is positioned between the two carbon nanotube functional layers. The carbon nanotube functional layers include at least two super-aligned carbon nanotube films disposed in a stacked manner.

[0020] Step S5: The composite film having the carbon nanotube functional layer formed thereon in step S4 is baked at high temperature to carbonize the positively charged carbonizable polymer in the composite film into amorphous carbon.

[0021] In step S1, the positively charged carbonizable polymer refers to a polymer whose surface has a positive zeta potential and can be decomposed into amorphous carbon when baked at high temperature. For example, the positively charged carbonizable polymer is polyaniline, chitosan, polydopamine, etc. In this embodiment, the positively charged carbonizable polymer is polyaniline.

[0022] In the nanosilicon whose surface is coated with a positively charged carbonizing polymer, the mass percentage of nanosilicon is preferably 40% to 50%. In this embodiment, the positively charged carbonizing polymer is polyaniline, and in the nanosilicon whose surface is coated with polyaniline, the mass percentage of nanosilicon is 45.5%.

[0023] The coating method of coating the positively charged carbonizing polymer on the surface of the nanosilicon material can be selected according to the specific material of the positively charged carbonizing polymer. In this embodiment, materials such as aniline, hydrochloric acid, and ammonium persulfate are used to coat the nanosilicon with polyaniline in situ in an ice-water mixed bath to obtain nanosilicon with a polyaniline surface (SiPA).

[0024] In this embodiment, the size of the nanosilicon is 20 nanometers to 80 nanometers. Of course, the size of the nanosilicon is not limited to the size of this embodiment, and may be other sizes of nanosilicon.

[0025] In step S2, the solvent is a solvent capable of dispersing the carbon nanotubes and the nanosilicon coated with the carbonizing polymer having a positive charge on the surface, such as ethanol, acetone, water, etc. In this embodiment, the solvent is ethanol.

[0026] Carbon nanotubes can be peeled off directly into a solvent from a superaligned array of carbon nanotubes (see Non-Patent Document 1). The superaligned array of carbon nanotubes is preferably placed on a substrate, and a knife or other tool can be used to peel off the carbon nanotube array from the substrate. The carbon nanotubes in the superaligned array of carbon nanotubes usually have a length of 300 microns or more, a diameter of 30 nanometers or less, and the alignment direction of the carbon nanotubes is basically the same. The surface of the carbon nanotubes in the superaligned array of carbon nanotubes is pure and basically does not contain impurities such as amorphous carbon or residual catalytic metal particles.

[0027] The amount of nanosilicon supported on nanosilicon coated with a positively charged carbonizing polymer is 1-5mg / cm 2 If the loading is too low, the capacity of the silicon anode is too small. If the loading is too high, the volume of the silicon anode changes significantly, the crushing problem becomes serious, and the capacity retention rate decreases. The preferred loading should take into account both the anode capacity and its retention rate. In this embodiment, the loading amount of nanosilicon in the nanosilicon surface-coated with polyaniline is 3 mg / cm. 2 It is.

[0028] The mass ratio of the carbon nanotubes to the nanosilicon coated with the positively charged carbonizing polymer on the surface is preferably 1: 2 to 1: 4. In this embodiment, the mass ratio of the carbon nanotubes to the nanosilicon coated with the positively charged carbonizing polymer on the surface is 1: 3.

[0029] In this embodiment, a cell ultrasonic crusher is used to perform ultrasonic dispersion. Of course, other ultrasonic devices may be used to perform ultrasonic dispersion, and the ultrasonic dispersion is not limited to the cell ultrasonic crusher of this embodiment.

[0030] The ultrasonic dispersion time can be set according to actual needs. For example, the size of the super-arranged carbon nanotube array and the power of ultrasonic dispersion affect the ultrasonic dispersion time. After the carbon nanotubes form a three-dimensional network structure in the solvent, the ultrasonic dispersion is stopped. The three-dimensional network structure is a fluffy structure. The fluffy structure is not only the carbon nanotubes entangled, but also a porous fluffy structure. After ultrasonic dispersion, the carbon nanotubes in the solvent form a continuous three-dimensional network structure, and the carbon nanotubes in the continuous three-dimensional network structure are uniformly distributed. Since the surface of the nanosilicon is coated with a positively charged carbonizing polymer, the zeta potential of the carbon nanotube is negative, and the carbon nanotube and the positively charged carbonizing polymer are non-uniformly charged, and the carbon nanotube and the nanosilicon modified with the positively charged carbonizing polymer are dispersed by their respective electrostatic repulsion forces, and anchored by their mutual electrostatic attraction forces. Therefore, the nanosilicon coated with the positively charged carbonizing polymer on the surface can be uniformly dispersed in the three-dimensional network structure formed by the carbon nanotubes and can be well bonded with the carbon nanotubes. The continuous three-dimensional network structure can simultaneously function as a mechanical support framework and a transport grid for electrons and lithium ions.

[0031] Referring to FIG. 2, we simulate the dispersion between nanosilicon (Si) and carbon nanotubes peeled off from SACNT arrays, and between nanosilicon (SiPA) whose surface is coated with polyaniline and carbon nanotubes peeled off from SACNT arrays, respectively. From FIG. 2, we can see that before being coated with polyaniline, the potential ranges from -3.9mV (Si) to 0mV (boundary), and Si moves away from CNT with electrostatic repulsion for 50ns, and the potential ranges from -1.6mV (CNT) to 6.4mV (SiPA), and SiPA approaches CNT with electrostatic attraction for 20ns. The simulation results show that Si and CNT with the same charge repel each other, and SiPA and SACNT with different charges attract each other, proving the effectiveness of the "dispersion anchor" strategy.

[0032] In step S3, after vacuum filtration, the resulting composite film of CNTs and nanosilicon coated with a positively charged carbonizable polymer is a flexible free-standing material. The three-dimensional network structure formed by the carbon nanotubes serves as a mechanical support framework, and the nanosilicon coated with a positively charged carbonizable polymer is uniformly dispersed in the three-dimensional network structure.

[0033] By changing the size and shape of the filtration membrane, composite membranes of different sizes and shapes can be obtained. Because the surface of nanosilicon is coated with a positively charged carbonizing polymer, the zeta potential of the carbon nanotube is negative, and the carbon nanotube and the positively charged carbonizing polymer are non-uniformly charged, and the carbon nanotube and the nanosilicon modified with the positively charged carbonizing polymer are dispersed by their respective electrostatic repulsion forces and anchored by their mutual electrostatic attraction forces. Therefore, the carbon nanotubes are dispersed with each other, and the carbon nanotubes and the positively charged carbonizing polymer attract each other to form a uniform composite membrane.

[0034] FIG. 3 is a schematic diagram of the manufacturing process of CNT@Si composite membrane and CNT@SiPA composite membrane. Here, @ indicates the combination of the two materials before and after. The meaning of @ is the same below. From FIG. 3, in the CNT@Si composite membrane, the nanosilicon and the carbon nanotube are not combined but are separated, and the aggregation phenomenon between the nanosilicon is relatively serious, while in the CNT@SiPA composite membrane, the nanosilicon is well combined with the surface of the carbon nanotube, the nanosilicon does not aggregate between them, and the dispersion is relatively uniform.

[0035] In step S4, preferably, among the at least two super-aligned carbon nanotube films stacked, the carbon nanotubes in the adjacent two super-aligned carbon nanotube films cross each other. The crossing angle of the carbon nanotubes in the adjacent two super-aligned carbon nanotube films is not limited. In this embodiment, the crossing angle of the carbon nanotubes in the adjacent two super-aligned carbon nanotube films is 90 degrees.

[0036] The manufacturing process of the carbon nanotube functional layer specifically includes the following steps:

[0037] The carbon nanotube film is then drawn from the array of super-aligned carbon nanotubes by a drawing device, and the super-aligned carbon nanotube film is placed on a substrate, in this embodiment, the drawing device is a glass rod, and the substrate is a metal frame.

[0038] The substrate is rotated at a certain angle to draw out a continuous second super-aligned carbon nanotube film from the super-aligned carbon nanotube array, and the second super-aligned carbon nanotube film is placed on the surface of the first super-aligned carbon nanotube film. In this embodiment, the metal frame is rotated by 90 degrees.

[0039] When the carbon nanotube functional layer includes three or more layers of super-aligned carbon nanotube films arranged in a stacked and crossed manner, the above steps are repeated several times to obtain the carbon nanotube functional layer. In this embodiment, the above steps are repeated ten times, and the obtained carbon nanotube functional layer includes ten layers of super-aligned carbon nanotube films arranged in a stacked and crossed manner.

[0040] The carbon nanotube functional layer is first laid on a substrate. Then, the entire carbon nanotube functional layer laid on the substrate is laid on two surfaces of a composite film. Referring to FIG. 4, in some embodiments, after drawing out the super-aligned carbon nanotube film from the super-aligned carbon nanotube array, the super-aligned carbon nanotube film is directly laid on two surfaces of the composite film. After laying one layer of the super-aligned carbon nanotube film, the composite film is rotated to make the super-aligned carbon nanotube film in the carbon nanotube functional layer stack and cross.

[0041] The super-aligned carbon nanotube array is composed of a plurality of carbon nanotubes, which are parallel to each other and perpendicular to the surface of the substrate. The super-aligned carbon nanotube array is free of impurities, such as amorphous carbon and residual catalytic metal particles. The super-aligned carbon nanotube array is manufactured by adopting a chemical vapor deposition method. Please refer to Patent Document 1 for a method for manufacturing the super-aligned carbon nanotube array.

[0042] The super-aligned carbon nanotube film is composed of a plurality of carbon nanotubes. The plurality of carbon nanotubes are aligned in the same direction. Aligning in the same direction means that the overall extension direction of most of the carbon nanotubes in the super-aligned carbon nanotube film is basically the same direction. And the overall extension direction of most of the carbon nanotubes is basically parallel to the surface of the super-aligned carbon nanotube film. Of course, microscopically, in the super-aligned carbon nanotube film, in addition to the plurality of carbon nanotubes aligned along the same direction, there are also carbon nanotubes aligned in random directions that are not aligned along the same direction. Here, the proportion of such carbon nanotubes aligned in random directions is small compared to the plurality of carbon nanotubes aligned along the same direction. Therefore, such carbon nanotubes aligned in random directions do not significantly affect the overall alignment of most of the carbon nanotubes in the super-aligned carbon nanotube film. Specifically, in the super-aligned carbon nanotube film, most of the carbon nanotubes aligned in the same direction are not completely straight, but can be bent appropriately, or they are not completely aligned in the extension direction, but can be appropriately deviated from the extension direction. Therefore, in the super-aligned carbon nanotube film, among the multiple carbon nanotubes aligned in substantially the same direction, the possibility cannot be denied that the parallel carbon nanotubes partially contact each other.

[0043] The carbon nanotube functional layer may have a thickness of 100 nm or less, and the thickness of the carbon nanotube functional layer may be 100 nm or less.

[0044] In step S5, the composite film is calcined at high temperature for a certain time to carbonize the positively charged carbonizable polymer in the composite film to amorphous carbon, thereby improving the electrical conductivity of the composite film. The temperature of the high temperature calcination is selected according to the cracking temperature of the positively charged carbonizable polymer. In this embodiment, the positively charged carbonizable polymer is polyaniline, which is calcined at 900° C. for 3 hours.

[0045] The loading of nanosilicon in the resulting composite material after calcination at high temperature is preferably 1.2 mg / cm 2 ~2mg / cm 2 It is.

[0046] Fig. 5 is a scanning electron microscope image of the cross section of the lithium ion battery anode obtained by the manufacturing method of this embodiment. From Fig. 5, it can be seen that the surface of the lithium ion battery anode is covered with a carbon nanotube functional layer and has a clean surface, which is because the high-temperature sintering process in the above manufacturing method does not damage the carbon nanotube functional layer.

[0047] It is understood that steps S4 and S5 are not necessary. In some embodiments, the method for manufacturing a lithium ion battery anode does not include steps S4 and S5. In other embodiments, the method for manufacturing a lithium ion battery anode includes only one of steps S4 or S5. All of these embodiments are within the scope of protection of the present invention.

[0048] The following describes in detail the specific steps of manufacturing the lithium ion battery anode in a specific embodiment of the present invention and the performance test of the lithium ion battery anode.

[0049] Embodiment 1: The method for preparing nanosilicon powder (Si-NH2) having amino groups grafted onto its surface is as follows.

[0050] Preparation of solution A: Mix 1.5 g of nanosilicon with a diameter of 20-80 nm with 250 ml of ethanol, and disperse by ultrasonic for 20 minutes. Preparation of solution B: Mix 15 ml of ammonia water with a concentration of 14.5 mol / L with 75 ml of deionized water. Slowly add solution B to solution A, and magnetically stir the mixture for 30 minutes. Drop 2.375 g of (3-aminopropyl)triethoxysilane (APTES) into the mixture and stir for 2 hours. Collect the complex by centrifugation, wash with ethanol several times, and dry the precipitate at 50 °C overnight. After collecting and grinding the precipitate, nanosilicon powder with amino groups grafted on the surface (Si-NH2) is obtained.

[0051] The method for preparing nanosilicon (SiPA) with its surface coated with polyaniline is as follows.

[0052] Preparation of solution C: 1.4g Si-NH2 and 200ml ethanol are mixed and sonicated for 15min, then 0.01mol aniline is added and sonication is continued for 30min. Preparation of solution D: 5.6g ammonium persulfate is dissolved in 40ml hydrochloric acid with a concentration of 1.4mol / L. Solution D is slowly added to solution C at 0℃, and magnetic stirring is maintained at 0℃ for 4h to allow polyaniline to coat the surface of Si-NH2 in situ. The mixture is washed by centrifugation several times, and the collected precipitate is dried at 50℃ overnight and crushed to obtain SiPA.

[0053] It is fired at high temperature to form amorphous carbon coated nanosilicon (SiPAC).

[0054] A tubular furnace is employed under argon atmosphere to heat the SiPA and hold it at 900°C for 3 hours to obtain amorphous carbon-coated nanosilicon (SiPAC) after the PANI is pyrolyzed.

[0055] CNT@Si, CNT@Si-membrane, CNT@SiPA, CNT@SiPA-membrane, CNT@SiPAC, and CNT@SiPAC-membrane were fabricated, where @ denotes the combination of the two materials before and after it.

[0056] The SACNT arrays are fabricated by chemical vapor deposition using iron as catalyst and acetylene as precursor. The CNTs in the SACNT arrays are 30 nm in diameter and 300 μm in height. The clean walls and strong intermolecular forces of the CNTs in the SACNT arrays lead to continuous super-aligned CNT films from the SACNT arrays via an end-to-end connection mechanism.

[0057] 30 mg of silicon, 10 mg of CNTs peeled off from the SACNT array, and 60 ml of ethanol are mixed, sonicated for 30 min, and vacuum filtered to obtain the CNT@Si composite. Each surface of the CNT@Si is covered with 10 layers of SACNT film arranged in a vertical cross-stack to obtain the CNT@Si-membrane. The mass loading of CNT@Si in the CNT@Si and CNT@Si-membrane is about 3 mg / cm. 2 It is.

[0058] Using the same steps as above, 30 mg of SiPA and 10 mg of CNTs peeled off from the SACNT array are employed to obtain CNT@SiPA. The two surfaces of the CNT@SiPA are covered with 10 layers of SACNT films arranged in a perpendicular cross-stack to obtain CNT@SiPA-membranes. The CNT@SiPA and CNT@SiPA-membranes are calcined (same calcination steps as those for producing SiPAC) to obtain CNT@SiPAC and CNT@SiPAC-membranes, in which the mass loading of Si is 1.2 mg / cm. 2 ~2mg / cm 2 It is.

[0059] The SiPA prepared in embodiment 1 is SiPA 0.01 and SiPAC is defined as 0.01 and CNT@SiPAC is defined as CNT@SiPAC 0.01 It is defined as follows.

[0060] Embodiment 2: This embodiment is basically the same as embodiment 1, and the difference is that different amounts of PANI are coated on Si-NH2 with 0.005 mol of aniline, and SiPA 0.005 The aim of the present invention is to prepare

[0061] SiPA 0.005 The SiPAC was then heat-treated in the same manner as in the first embodiment. 0.005 The CNT@SiPA was obtained in the same manner as in the first embodiment. 0.005 and CNT@SiPA 0.005 - Obtain the membrane.

[0062] Embodiment 3: This embodiment is basically the same as embodiment 1, and the difference is that different amounts of PANI are coated on Si-NH2 with 0.015 mol of aniline, and SiPA 0.015 The aim of the present invention is to prepare

[0063] SiPA 0.015 The SiPAC was then heat-treated in the same manner as in the first embodiment. 0.015 The CNT@SiPA was obtained in the same manner as in the first embodiment. 0.015 and CNT@SiPA 0.015 - Obtain the membrane.

[0064] Referring to FIG. 6, the SiPA in the first to third embodiments 0.01 , SiPA 0.005 and SiPA 0.015 The mass percentages of nanosilicon in are 45.5%, 51.1% and 39.4%, respectively.

[0065] Comparative Example 1 Preparation of silicon slurry electrodes Nanosilicon, conductive carbon black, and CMC are mixed in water with a weight ratio of 8:1:1, and then coated onto a copper foil current collector to obtain a uniform slurry. After drying at 60°C for 2 hours and transferring to a 120°C oven to remove moisture, a Si electrode sheet (Si slurry electrode) is obtained. The Si electrode sheet is used for bending performance test.

[0066] The electrodes of CNT@Si, CNT@Si-membrane, CNT@SiPA, CNT@SiPA-membrane, CNT@SiPAC, CNT@SiPAC-membrane and Si-slurry obtained in the above embodiments 1 to 3 and comparative example 1 are cut into disks with a diameter of 10 mm to obtain flexible electrodes without additional adhesives or current collectors. The specific capacitance is calculated based on the mass of Si.

[0067] To test the performance of the lithium-ion battery anode of the present invention, CNT@Si, CNT@SiPA, CNT@SiPAC, CNT@Si-membrane, CNT@SiPA-membrane and CNT@SiPAC-membrane are used as anodes, lithium foil as cathodes, and commercial PP films as separators, and 1 mol / L lithium hexafluorophosphate (LiPF6) is added to a non-aqueous solvent of fluoroethylene carbonate (FEC), hydrofluoroether (HFE) and fluoroethyl methyl carbonate (FEMC) with a mass percentage of 2:6:2 to form an electrolyte, and a button battery is assembled in a CR2025 battery case. The button battery assembly process is carried out in an argon glove box.

[0068] Referring to FIG. 7, the button batteries assembled from the anodes of CNT@Si, CNT@Si-membrane, CNT@SiPAC, and CNT@SiPAC-membrane in embodiment 1 were first charged with 0.2Ag -1 The battery is then activated by repeating charge and discharge five times at a current density of 0.4Ag. -1 From Figure 7, the button battery assembled with the CNT@Si anode has an initial specific capacity of 2453.5 mAhg -1 After 50 charge / discharge cycles, the specific capacity was only 242.2mAhg. -1 The CNT@Si anode exhibited a slightly higher specific capacity than the CNT@Si anode because the cross-stacked SACNT films on both sides reduced the loss of active material; however, the specific capacity was only 327.9 mAhg after 50 charge / discharge cycles. -1It can be seen that the coulombic efficiency of the CNT@Si anode and the CNT@Si film anode is unstable during cycling. This is probably because the cracked nanosilicon exposes new interfaces in contact with the electrolyte, consuming the electrolyte excessively. From Figure 7, the button cells assembled with the CNT@SiPAC anode and the CNT@SiPAC-film anode have an initial specific capacity of 2199.5 mAhg, respectively. -1 and 2380.4mAhg -1 After 200 charge / discharge cycles, the specific capacity was 1046.1mAhg -1 and 1170.4mAhg -1 It can be seen that the Coulombic efficiency is maintained. Furthermore, the Coulombic efficiency is stable during charging and discharging (cycling) after the nanosilicon coating is subjected to high-temperature treatment. These results indicate that the capacity fade of the silicon anode can be effectively suppressed by modifying the nanosilicon surface with a coating.

[0069] FIG. 8 shows the CNT@SiPAC in the first to third embodiments. 0.01 -Membrane, CNT@SiPAC 0.005 -Membrane and CNT@SiPAC 0.015 8 is a graph showing the cycle performance of a button battery obtained by using the CNT@SiPAC-film anode. 0.05 -Membrane, CNT@SiPAC 0.01 -Membrane and CNT@SiPAC 0.015 -The initial specific capacity of the membrane anode is 2110.1mAhg, respectively. -1 , 2380.4mAhg -1 and 3357.5mAhg -1 It can be seen that 0.4Ag -1 After 200 charge / discharge cycles, the specific capacity of the three anodes was 735.3mAhg, respectively. -1 , 1170.4mAhg -1 and 916.8mAhg -1 The results are shown in Table 1. 0.01 -The membrane shows the best cycle performance.

[0070] Figure 9 shows that the area loading of silicon in the anode CNT@SiPAC membrane is 1.19 mg / cm 2 , 1.38 mg / cm 2 , 1.72 mg / cm 2 and 1.99 mg / cm 2 From FIG. 9, the areal capacity of the first charge / discharge cycle is 2.84 mAh cm -2 , 4.60mAhcm -2 , 6.92mAhcm -2 and 8.34mAhcm -2 and 0.4Ag -1 After 100 charge / discharge cycles at a current density of 1.92 mAhcm -2 , 2.45mAhcm -2 , 2.75mAhcm -2 and 2.87mAhcm -2 It can be seen that the anode of the CNT@SiPAC-membrane of the present invention has a better cycle performance.

[0071] The above test results in Figures 7 to 9 show that after the nanosilicon of the present invention is coated with PANI coating, the composite of nanosilicon and carbon nanotubes becomes more uniform, the uniformity of the anode is improved, and the carbon nanotube functional layer reduces the loss of active material, effectively improving the cycle stability of the anode of CNT@SiPAC-membrane. At the same time, the diffusion coefficient D of lithium ions can be improved by high-temperature sintering. Li+ increases, and the contact resistance R1 and the interfacial charge transfer resistance R ct The three-dimensional network structure of the carbon nanotube structure provides sufficient electron conduction network and ion diffusion channels, which can realize faster reaction kinetics and exhibit better magnification performance.

[0072] Referring to FIG. 10, when the current density is 0.2Ag -1 , 0.4Ag -1 , 0.8Ag -1 , 2.0Ag -1 and 4.0Ag -1The specific capacitance of the CNT@SiPAC-film anode is 2344.9mAhg, respectively. -1 , 2207mAhg -1 , 1849.4mAhg -1 , 1539.2mAhg -1 and 1249.7mAhg -1 The current density is 4.0Ag -1 From 0.2Ag -1 When the battery recovers to 100%, the discharge capacity is 2351.5mAhg. -1 From Fig. 10, the capacity of the CNT@SiPAC anode is lower than that of the CNT@SiPAC-membrane anode, and the current density is 0.2A g -1 When the initial specific capacity is 2039.2mAhg -1 and the current density is 4.0Ag -1 From 0.2Ag -1 When the specific capacity of the CNT@SiPAC anode was recovered to 1933.1 mAhg -1 It can be seen that the capacity retention is 94.79%, which is lower than that of the CNT@SiPAC-membrane anode. This indicates the effectiveness of the cross-stacked SACNT film. The carbon nanotube functional layer of the CNT@SiPAC-membrane anode of the present invention can effectively reduce the loss of active materials. From FIG. 10, it can be seen that the CNT@Si and CNT@Si-membrane anodes have poor multiplication performance and a current density of 4.0A g -1 When the specific capacity is 17.0mAhg, -1 and 31.1mAhg -1 The current density is 0.2Ag -1 When the capacity of the CNT@Si anode is recovered to 0.2V, the capacity retention rate of the CNT@Si anode is only 68.36%, and that of the CNT@Si-membrane anode is only 68.54%. This indicates that rapid alloying / dealloying has a great impact on the electrochemical performance of nanosilicon. Figure 10 shows that the CNT@SiPAC-membrane anode has the best multiplication performance, and the scheme of PANI coating layer, carbonization, and carbon nanotube functional layer can achieve fast reaction kinetics.

[0073] Referring to FIG. 11, the current density of the SiPAC / / Li pouch battery assembled with the CNT@SiPAC membrane was 0.4A g -1 In this case, the capacity after the first charge / discharge cycle is 36.69 mAh, and the capacity retention rate after 50 charge / discharge cycles is 86.9%, which shows great commercial potential.

[0074] Referring to FIG. 12, a normalized resistance change graph measured in real time using a bending life tester to perform long-term (repeated) bending of the CNT@SiPAC-film electrode of embodiment 1 and the Si-slurry electrode of comparative example 1 at 90° and 180°. From FIG. 12, it can be seen that the resistance of the CNT@SiPAC-film electrode hardly changes over a long period of time, and the resistance increase after 10,000 bending at 90° is 2.66%, and the resistance increase after 10,000 bending at 180° is 3.14%. This shows that the carbon nanotubes build a flexible and strong mechanical framework, which allows the film to withstand long-term bending at large angles. Conversely, the Si-slurry electrode is very poor at bending, and the resistance increases by 779% after nine bendings at 90° and 994% after three bendings at 180°, and then increases sharply to indicate a short circuit. These results demonstrate the superior flexibility and durability of the CNT@SiPAC-membrane electrodes of the present invention compared to conventional electrodes using slurry and metal current collectors.

[0075] The pre-lithiated CNT@SiPAC-film anode and the CNT@LFP thin film cathode are assembled to fabricate a SiPAC / / LFP pouch battery for bending capacity retention test. Referring to FIG. 13, the SiPAC / / LFP pouch battery has a charge capacity of 60.12mAh and a discharge capacity of 56.43mAh during the first charge / discharge process. Because of pre-lithiated, the initial coulombic efficiency is 93.9%. Then, the pouch battery is bent at 90° for 10,000 times. After bending, the pouch battery still has the same appearance, and the charge capacity is 57.84mAh and the discharge capacity is 54.48mAh. The 96.2% charge capacity retention and 96.5% discharge capacity retention of the SiPAC / / LFP pouch battery prove that the CNT@SiPAC-film anode has excellent flexibility.

[0076] The method for manufacturing the anode of the lithium ion battery provided by the present invention provides a method for manufacturing a flexible nanosilicon anode from two aspects: surface modification and structural design. The positively charged carbonizable polymer is coated on the surface of the nanosilicon, and the effect of "dispersion anchor" between the positively charged carbonizable polymer and the negatively charged carbon nanotubes improves the uniformity of the anode. The amorphous carbon derived from the positively charged carbonizable polymer can solve the technical problems such as anode cracking and rapid capacity decline caused by the nanosilicon undergoing serious volume change during cycling, the problem of nanosilicon aggregation, and the low electrical conductivity and slow electrode dynamics of nanosilicon. With the carbon nanotube functional layer, the anode of the CNT@SiPAC-film does not require additional adhesives, conductive agents and current collectors, and under the same specific capacity and total capacity, the lithium ion battery of the present invention has a smaller mass. The carbon nanotube film provides sufficient electron transport network, ion diffusion channels, reserved space for silicon volume expansion, and strong three-dimensional mechanical support. In addition, the CNT functional layers located on both sides of the composite membrane can effectively reduce the detachment of active materials from the electrode surface. Moreover, the nanosilicon anode obtained by this manufacturing method exhibits excellent flexibility and can be bent freely.

[0077] Referring to FIG. 14, an embodiment of the present invention further provides a lithium ion battery anode 100. The lithium ion battery anode 100 includes a carbon nanotube three-dimensional network structure 102, a plurality of amorphous carbon-coated nanosilicon particles 104, and two carbon nanotube functional layers 106. The plurality of amorphous carbon-coated nanosilicon particles 104 are uniformly distributed in the carbon nanotube three-dimensional network structure 102, and the plurality of amorphous carbon-coated nanosilicon particles 104 are attached to the surface of the carbon nanotubes in the carbon nanotube three-dimensional network structure 102. The two carbon nanotube functional layers 106 are respectively disposed on two opposite surfaces of the carbon nanotube three-dimensional network structure 102, and the carbon nanotube three-dimensional network structure 102 is located between the two carbon nanotube functional layers. The lithium ion battery anode 100 is flexible and self-supporting, and can be freely bent. Amorphous carbon is obtained by calcining a positively charged carbonizable polymer at high temperatures in the manufacturing process of lithium-ion battery anodes.

[0078] A positively charged carbonizable polymer refers to a polymer that has a positive surface zeta potential and can be decomposed into amorphous carbon when baked at high temperature. For example, the positively charged carbonizable polymer is polyaniline, chitosan, polydopamine, etc. In this embodiment, the positively charged carbonizable polymer is polyaniline.

[0079] In this embodiment, the size of the nanosilicon is 20 nanometers to 80 nanometers. Of course, the size of the nanosilicon is not limited to the size of this embodiment, and may be other sizes of nanosilicon.

[0080] In the lithium ion battery anode 100, the mass loading of nanosilicon is preferably 1.2 mg / cm 2 ~2mg / cm 2 It is.

[0081] The three-dimensional carbon nanotube network structure 102 is a fluffy structure. The fluffy structure is not only the carbon nanotubes intertwined, but also a porous fluffy structure. The three-dimensional carbon nanotube network structure 102 has a number of micropores, which promotes the infiltration of electrolyte and improves the lithium ion battery anode 100's ability to absorb and desorb lithium ions, and the micropores are used to accommodate lithium ions, so that when the lithium ion battery anode 100 of the present invention is used in a lithium ion battery, its volume does not increase significantly.

[0082] The carbon nanotube functional layer 106 includes at least two super-aligned carbon nanotube films arranged in a stacked manner, and the carbon nanotubes in the two adjacent super-aligned carbon nanotube films are arranged in a cross-arrangement. The cross angle of the carbon nanotubes in the two adjacent super-aligned carbon nanotube films is not limited. In this embodiment, the carbon nanotube functional layer 106 includes 10 layers of super-aligned carbon nanotube films arranged in a stacked manner, and the cross angle of the carbon nanotubes in the adjacent super-aligned carbon nanotube films is 90°.

[0083] The three-dimensional network structure 102 of carbon nanotubes, the amorphous carbon coated nanosilicon particles 104, and the carbon nanotube functional layer 106 in this embodiment are all the same as those described in the manufacturing method for the anode of a lithium ion battery, and include all the technical features described in the manufacturing method for the anode of a corresponding lithium ion battery, which will not be repeated here.

[0084] Referring to Fig. 15, another embodiment of the present invention provides a lithium ion battery anode 200. The lithium ion battery anode 200 includes a three-dimensional carbon nanotube network structure 202 and a plurality of nanosilicon particles 204 coated with a positively charged carbonizing polymer. The nanosilicon particles 204 coated with a positively charged carbonizing polymer are uniformly distributed in the three-dimensional carbon nanotube network structure 202, and the nanometer silicon particles 204 coated with a positively charged carbonizing polymer are attached to the surface of the carbon nanotubes in the three-dimensional carbon nanotube network structure 202.

[0085] A positively charged carbonizable polymer refers to a polymer whose surface has a positive zeta potential and can be decomposed into amorphous carbon when baked at high temperature. For example, the positively charged carbonizable polymer is polyaniline, chitosan, polydopamine, etc. In this embodiment, the positively charged carbonizable polymer is polyaniline.

[0086] In the nanosilicon particles 204 coated with a positively charged carbonizable polymer, the mass percentage of nanosilicon is preferably 40% to 50%. In this embodiment, the positively charged carbonizable polymer is polyaniline, and the mass percentage of nanosilicon in the nanosilicon having a polyaniline-coated surface is 45.5%.

[0087] The amount of nanosilicon carried in the nanosilicon particles 204 whose surfaces are coated with a positively charged carbonizable polymer is preferably 1 to 5 mg / cm 2 If the loading is too low, the capacity of the silicon anode is too small, and if the loading is too high, the volume of the silicon anode changes significantly, the crushing problem becomes serious, and the capacity retention rate is reduced. This preferred loading should take into account both the capacity of the anode and its retention rate. In this embodiment, the loading amount of nanosilicon in the nanosilicon particles 204 whose surfaces are coated with polyaniline is 3 mg / cm. 2 It is.

[0088] The mass ratio of the three-dimensional network structure 202 of carbon nanotubes to the nanosilicon particles 204 whose surfaces are coated with a positively charged carbonizing polymer is preferably 1:2 to 1:4. In this embodiment, the mass ratio of the carbon nanotubes to the nanosilicon whose surfaces are coated with lyaniline is 1:3.

[0089] In this embodiment, the size of the nanosilicon is 20 nanometers to 80 nanometers. Of course, the size of the nanosilicon is not limited to the size of this embodiment, and may be other sizes of nanosilicon.

[0090] The three-dimensional carbon nanotube network structure 202 is a fluff structure. The fluff structure is not only the carbon nanotubes intertwined, but also a porous fluffy structure. The three-dimensional carbon nanotube network structure 202 has a number of micropores, which facilitates the infiltration of electrolyte and improves the lithium ion battery anode 200's ability to absorb and desorb lithium ions, and the micropores are used to accommodate lithium ions, so that when the lithium ion battery anode 200 of the present invention is used in a lithium ion battery, its volume does not increase significantly.

[0091] The lithium ion battery anode 200 is flexible, self-supporting, and can be bent freely.

[0092] The lithium ion battery anode 200 further includes two carbon nanotube functional layers (not shown), which are respectively disposed on two opposite surfaces of the carbon nanotube three-dimensional network structure 202, and the carbon nanotube three-dimensional network structure 202 is located between the two carbon nanotube functional layers. The carbon nanotube functional layer includes at least two super-aligned carbon nanotube films disposed in a stacked manner, and the carbon nanotubes in the two adjacent super-aligned carbon nanotube films are disposed in a cross-arranged manner. In this embodiment, the carbon nanotube functional layer includes 10 layers of super-aligned carbon nanotube films disposed in a stacked manner, and the cross angle of the carbon nanotubes in the adjacent super-aligned carbon nanotube films is 90 degrees.

[0093] The three-dimensional network structure 202 of carbon nanotubes, the nanosilicon particles 204 coated with a positively charged carbonizable polymer, and the two carbon nanotube functional layers and the positively charged carbonizable polymer in this embodiment are all the same as those described in the manufacturing method for a lithium ion battery anode, and include all the technical features described in the manufacturing method for a corresponding lithium ion battery anode, which will not be repeated here.

[0094] The lithium ion battery anode obtained by adopting the manufacturing method of the lithium ion battery anode provided by the present invention has high uniformity. The amorphous carbon derived from the positively charged carbonizable polymer can solve the technical problems such as anode cracking and rapid capacity decline caused by nanosilicon undergoing serious volume change in charge-discharge cycles, the problem of nanosilicon aggregation, and the low electrical conductivity and slow electrode dynamics of nanosilicon. With the carbon nanotube functional layer, the lithium ion battery anode does not require additional adhesives, conductive agents and current collectors, saving energy and further reducing the volume and weight of the anode. The three-dimensional network structure of the carbon nanotubes provides sufficient electron transport network, ion diffusion channels, reserved space for silicon volume expansion, and strong three-dimensional mechanical support. In addition, the CNT functional layers located on both sides of the composite film can effectively reduce the detachment of active materials from the electrode surface. In addition, the lithium ion battery anode exhibits excellent flexibility. Due to the three-dimensional network structure of the carbon nanotubes and the presence of multiple micropores in the carbon nanotube functional layer, the lithium ion adsorption and deintercalation ability of the anode of the lithium ion battery is improved, and since the micropores are used to accommodate the lithium ions, the volume of the lithium ion battery of the present invention does not increase significantly when it is used.

[0095] In addition, those skilled in the art can make other modifications within the spirit of the present invention. Of course, all of these modifications made according to the spirit of the present invention should be included in the scope of the protection claims of the present invention. [Explanation of symbols]

[0096] 100, 200 Lithium-ion battery anode 102, 202 Three-dimensional network structure of carbon nanotubes 104 Nanosilicon particles coated with amorphous carbon 106 Carbon nanotube functional layer 204 Multiple nanosilicon particles coated with a positively charged carbonizable polymer

Claims

1. The present invention relates to a method for manufacturing a semiconductor device comprising: forming a three-dimensional network structure of carbon nanotubes; forming a plurality of nanosilicon particles coated with amorphous carbon; and forming a functional layer of two carbon nanotubes; The three-dimensional network structure of the carbon nanotubes is composed of a plurality of entangled carbon nanotubes, and two surfaces of the three-dimensional network structure of the carbon nanotubes that are opposite to each other are defined as a first surface and a second surface; A plurality of the nanosilicon particles coated with amorphous carbon are dispersed in the three-dimensional network structure of the carbon nanotubes and attached to the surfaces of the carbon nanotubes in the three-dimensional network structure of the carbon nanotubes; The two carbon nanotube functional layers are respectively laid on the first and second surfaces of the three-dimensional network structure of the carbon nanotubes, so that the three-dimensional network structure of the carbon nanotubes is positioned between the two carbon nanotube functional layers, and the carbon nanotube functional layers include at least two layers of hyper-aligned carbon nanotube films stacked and cross-arranged.

2. The mass loading of the nanosilicon particles is 1.2 mg / cm 2 ~2mg / cm 2 2. The anode of claim 1 during discharge of a lithium ion battery.

3. The present invention relates to a method for manufacturing a carbon nanotube-based semiconductor device, and more particularly to a method for manufacturing the same. the three-dimensional network structure of the carbon nanotubes is composed of a plurality of entangled carbon nanotubes; a plurality of said nanosilicon particles coated with a positively charged carbonizing polymer are dispersed in the three-dimensional network structure of said carbon nanotubes and are attached to the surfaces of the carbon nanotubes in the three-dimensional network structure of said carbon nanotubes; The two carbon nanotube functional layers are disposed on two opposing surfaces of the three-dimensional carbon nanotube network structure, respectively; The anode of a lithium ion battery during discharge is characterized in that the three-dimensional network structure of the carbon nanotubes is located between the two carbon nanotube functional layers.

4. Two surfaces facing each other in the three-dimensional network structure of the carbon nanotubes are defined as a first surface and a second surface; The positive electrode of claim 3, wherein the two carbon nanotube functional layers are respectively laid on the first surface and the second surface of the three-dimensional network structure of the carbon nanotube, and the carbon nanotube functional layer comprises at least two layers of super-aligned carbon nanotube films stacked and cross-arranged.

Citation Information

Patent Citations

  • Lithium ion battery negative plate with high-capacity negative electrode bonding system and battery

    CN112201788A

  • Silicon-carbon composite material and preparation method thereof, negative electrode material, negative electrode plate and lithium ion battery

    CN113241439A

  • Carbon nano pipe rpoe and preparation method thereof

    CN1483667A

  • Li-ion battery electrodes having nanoparticles in a conductive polymer matrix

    US20140045065A1

  • Negative electrode for secondary battery, and secondary battery

    WO2022070895A1